Cancer risks in Fanconi anemia: findings from the German Fanconi Anemia Registry - Philip S. Rosenberg; Blanche P. Alter; Wolfram Ebell (Haematologica, 2008)
Background Fanconi anemia is an inherited genomic instability syndrome associated with progressive bone marrow failure leading to death or the requirement for hematopoietic stem cell transplantation, acute myeloid leukemia, and solid tumors. Prior epidemiological studies have quantified the risks of bone marrow failure, acute myeloid leukemia and solid tumors, but these estimates have not been replicated.Design and Methods We assembled a cohort of 181 patients with Fanconi anemia mostly from Germany. We calculated the ratio of observed to expected cancers, and the risks of bone marrow failure, acute myeloid leukemia, and solid tumors by age.Results The first adverse event was bone marrow failure in 66 patients, acute meyloid leukemia in 14 patients and solid tumors in 10 patients. The ratio of observed to expected cancers was 44 for all cancers, 26 for all solid tumors, and 868 for acute myeloid leukemia; these increased risks were statistically significant. Significantly elevated ratios of observed to expected cancers were observed for esophageal (6281), vulvar (2411), head and neck (240), breast (34) and brain (23) tumors. Absent or abnormal radii, and a five-item congenital abnormality score, were significant risk factors for bone marrow failure. The cumulative incidence of bone marrow failure by the age of 10 years varied from 12.6% in the lowest bone marrow failure risk group to 84% in the highest. The relative hazard of bone marrow failure was significantly higher in complementation group G versus A (relative hazard=2.2) and in C versus A (relative hazard=5.4).Conclusions Findings from the German Fanconi Anemia Registry cohort validate prior risk estimates, and strongly support the concept that Fanconi anemia is a highly penetrant cancer susceptibility syndrome with early onset of acute myeloid leukemia and slightly later onset of specific solid tumors.